A Turkish family with Greig cephalopolysyndactyly syndrome - Boduroğlu, Koray; Balci, Sevim; Topçu, Meral (The Turkish Journal of Pediatrics, 1999)
Greig cephalopolysyndactyly syndrome is a very rare autosomal dominant disease characterized by postaxial polysyndactyly of hands, preaxial polysyndactyly of feet and peculiar facial features, and has been shown to be due to mutations in the GLI3 gene. We present clinical findings of a 39-year-old man and his nine-day-old daughter with Greig cephalopolysyndactyly who showed variable expression with regard to syndactyly of fingers and toes. The role of obstetric ultrasonography in the prenatal diagnosis of the syndrome is also discussed.